2016
DOI: 10.1002/2015wr018375
|View full text |Cite
|
Sign up to set email alerts
|

Water and sanitation service delivery, pricing, and the poor: An empirical estimate of subsidy incidence in Nairobi, Kenya

Abstract: The increasing block tariff (IBT) is among the most widely used tariffs by water utilities, particularly in developing countries. This is due in part to the perception that the IBT can effectively target subsidies to low-income households. Combining data on households' socioeconomic status and metered water use, this paper examines the distributional incidence of subsidies delivered through the IBT in Nairobi, Kenya. Contrary to conventional wisdom, we find that high-income residential and nonresidential custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 25 publications
2
47
0
Order By: Relevance
“…The conclusion recommended the following; the poor to receive connections, subsidies, public taps, and recognition of water vending including control of private operators. Recent scholars on the same issue like [133] [134] added their voice on the same theme by stating that the water tariff structure must contain, use volume, service level type, unit cost, waste service, tariff structure and socio-economic status of the user.…”
Section: Related Work On the Implication Of Unreliable Water Supplymentioning
confidence: 99%
“…The conclusion recommended the following; the poor to receive connections, subsidies, public taps, and recognition of water vending including control of private operators. Recent scholars on the same issue like [133] [134] added their voice on the same theme by stating that the water tariff structure must contain, use volume, service level type, unit cost, waste service, tariff structure and socio-economic status of the user.…”
Section: Related Work On the Implication Of Unreliable Water Supplymentioning
confidence: 99%
“…Hence, this paper explores these three ID pillars of governance approaches: (A) social, (B) environmental and (C) relational (Gupta et al, 2015;Gupta & Vegelin, 2016), linking them to six WatSan indicators: (A.1) access to minimum WSS (as a right) (Appelblad Fredby & Nilsson, 2013;Bisung et al, 2016), (A.2) access to WSS even if the urban poor do not have formal housing (Obrist et al, 2006;Appelblad Fredby & Nilsson, 2013), (B.1) domestic wastewater collection and treatment (Heller, 2009;Oteng-Ababio, 2014), (B.2) water availability (for WSS delivery) Giatti et al, 2013;Heller, 2015), (C.1) participation (of the urban poor) (Obrist et al, 2006;Bisung et al, 2016) and (C.2) low-income WSS subsidies (Attari & van Dijk, 2016;Fuente et al, 2016). The indicators selected potentially address exclusion, reflecting key issues of concern to the urban poor (Obrist et al, 2006;Oteng-Ababio, 2014;Chimankar, 2016;Murungi & Blokland, 2016b).…”
Section: Inclusive Discourses Inclusive Development Dimensions and Wmentioning
confidence: 99%
“…[] included multiple or nonlinear tariffs, while 74% of water utilities in developing countries use IBT schemes according to Fuente et al . []. Understanding the role played by the functional form in the determination of price elasticity is relevant to policy makers for the development of water policies.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing block tariff (IBT) schemes are very common in the literature. For instance, more than 40% of the studies reported by Dalhuisen et al [2003] included multiple or nonlinear tariffs, while 74% of water utilities in developing countries use IBT schemes according to Fuente et al [2016]. Understanding the role played by the functional form in the determination of price elasticity is relevant to policy makers for the development of water policies.…”
Section: Introductionmentioning
confidence: 99%